Geopolitics, geography, and strategic history - Sloan, G. R. (Geoffrey R.) (Geopolitical theory series, 2017)
This book addresses three interrelated questions: why does the geographical scope of political objectives and subsequent strategy of states change? How do these changes occur? Over what period of time do these changes occur? The theories of Sir Halford Mackinder and Nicholas Spykman are examined in order to provide an analytical narrative for five case studies, four historical and one contemporary. Taken together they offer the prospect of converting descriptions of historical change into analytic explanations, thereby highlighting the importance of a number of commonly overlooked variables. In addition, the case studies will illuminate the challenges that states face when attempting to change the scope of their foreign policy and geo-strategy in response to shifts in the geopolitical reality. This book breaks new ground in seeking to provide a way to understand why and how the geographical scope of political objectives and subsequent strategy both expands and contracts.